META-ANALISIS: EFEKTIFITAS PEMBERIAN PAKAN BUATAN UNTUK MENINGKATKAN LAJU PERTUMBUHAN DAN KUALITAS REPRODUKSI SPESIES Monopterus albus - Santosa, Tomi Apra; Putri, Rani Dwi Suci; Sumarmin, Ramadhan; Putri, Dwi Hilda (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
This study aims to determine the effectiveness of artificial feeding on the growth and reproduction rate of Monopterus Albus species. This research is meta-analysis research. The data source comes from a search of 18 national and international articles published in 2010-2020 related to feeding the Monopterus albus species. Data obtained from google scholar database, DOAJ, ScienceDirect, sagejournal, Springer, and IEEE. The data analysis technique is a qualitative descriptive analysis with JASP software. The results showed that 35% of artificial feeding affected the growth of Monopterus albus and 28.5% affected the reproductive rate with an effect size of 1.2. This shows that artificial feeding is effective in increasing the growth and reproductive quality of Monopterus albus.